SHORT COMMUNICATION Mapping Flood Risk Assessment by Remote Sensing in District Chiniot, Pakistan: SHORT COMMUNICATION Mapping Flood Risk Assessment by Remote Sensing in District Chiniot, Pakistan - Ahmad, Mirza Naseer; Salahuddin, Maria; Sultana, Rashida (International Journal of Economic and Environmental Geology, 2024)
SHORT COMMUNICATION Mapping Flood Risk Assessment by Remote Sensing in District Chiniot, Pakistan